Potential of non-commercial parts of Arracacia xanthorrhiza Bancroft: Biscuit production - Silva, Luan Ramos da; Jorge, Rosimeire Pereira Gassi; Torales, Elissandra Pacito; Vieira, Maria do Carmo; Heredia-Zárate, Néstor Antonio; Sanjinez-Argandoña, Eliana Janet (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
Some vegetables, such as Arracacia xanthorrhiza, present parts that are not commercialized. However, it still has a great composition that make it interesting to food industry. The flours production from vegetable waste are a great way to guarantee its use as a whole and decrease of waste of food in the World. Also, it can contribute on food products by adding nutrients and compounds important for human health. This study aimed to develop semi-sweet biscuits with crown and non-commercial roots of A. xanthorrhiza flour and the evaluation of its nutritional composition, physical characteristics and sensory profile. Biscuits were made in different concentration of cornmeal, flours of crowns and non-commercial roots of A. xanthorrhiza, according to centroid simplex experimental design, resulting in nine trials. The influence on nutritional, physical and sensory characteristics of the substitution of flours on the biscuits were analyzed. Results of the proximal composition of different formulations of biscuit were significantly different, except for lipids. Formulations with high percentage of flour of crown have presented darker color and has been liked by assessors on the sensory analyze, which could be associated with chocolate biscuits, due to the dark brown color. Semi-sweet biscuits with flour of crown and non-commercial roots of A. xanthorrhiza were satisfactory developed and showed a great nutritional composition, mainly on the minerals, fiber and carbohydrate content.